A New Dog - Hunt Roderick; Brychta Alex (China Oxford University Press, 2012)
Patterned Stories and More Patterned Stories. A practise vocabulary in the context of a repeated sentence structure to help develop confidence and fluency. Books contain inside cover notes to support children in their reading. Help with childrens reading development. The Stage 2 Biff, Chip and Kipper Stories provide a rich story context to help develop language comprehension and decoding skills. Stories, More Stories A and More Stories B offer a predictable sentence structure to support reading success.
Keywords: Englis-Oxford Reading Tree